HYDROMETRA IN A GOAT - MURUGAVEL, K; ANTOINE, D; RAJU, M S (The Indian Journal of Animal Reproduction, 2023)
A case of hydrometra in a goat and its ultrasonographic diagnosis and successful therapeutic management has been reported in the present paper.